2022
DOI: 10.3389/fendo.2022.900791
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Targeting Periostin in the Treatment of Graves’ Orbitopathy

Abstract: Periostin is a matricellular protein that is ubiquitously expressed in normal human tissues and is involved in pathologic mechanism of chronic inflammatory and fibrotic disease. In this study we investigate periostin in the pathogenesis of Graves’ orbitopathy (GO) using human orbital adipose tissue obtained from surgery and primary cultured orbital fibroblasts in vitro. POSTN (gene encoding periostin) expression in Graves’ orbital tissues and healthy control tissues was studied, and the role of periostin in GO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…41 Similarly, periostin knockdown decreased the expression of αSMA and Col1a1 in fibroblasts treated with TGF-β1. 30,42 On the other hand, some reports indicate that administration of periostin increases αSMA expression in fibroblasts, 43 while in other studies, periostin administration had no effect on αSMA expression in fibroblasts, 30,44 and a certain consensus has not been reached. The present study showed that FFSS-induced gene expression of both α-SMA and Col1a1 was suppressed by periostin knockdown, while periostin treatment did not increase the expression of these genes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…41 Similarly, periostin knockdown decreased the expression of αSMA and Col1a1 in fibroblasts treated with TGF-β1. 30,42 On the other hand, some reports indicate that administration of periostin increases αSMA expression in fibroblasts, 43 while in other studies, periostin administration had no effect on αSMA expression in fibroblasts, 30,44 and a certain consensus has not been reached. The present study showed that FFSS-induced gene expression of both α-SMA and Col1a1 was suppressed by periostin knockdown, while periostin treatment did not increase the expression of these genes.…”
Section: Discussionmentioning
confidence: 95%
“…Periostin knockout mice showed decreased αSMA and Col1a1 expression in in vivo models of scleroderma 30 and palatal wounds 41 . Similarly, periostin knockdown decreased the expression of αSMA and Col1a1 in fibroblasts treated with TGF‐β1 30,42 . On the other hand, some reports indicate that administration of periostin increases αSMA expression in fibroblasts, 43 while in other studies, periostin administration had no effect on αSMA expression in fibroblasts, 30,44 and a certain consensus has not been reached.…”
Section: Discussionmentioning
confidence: 98%